Risk Factors of Typhoid Fever in Adolescents in PKU Muhammadiyah Singkil Islamic Hospital, Tegal District - Wardani, Dita Pratiwi Kusuma (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Typhoid fever is an acute infectious disease of the small intestine caused by the bacteria Salmonella typhi or Salmonella paratyphi A, B, and C. Various factors influence the occurrence of typhoid fever, including handwashing habits, consuming snacks outside the home, and environmental conditions around the house. This study aims to determine the risk factors for the incidence of typhoid fever in adolescents at PKU Muhammadiyah Singkil Hospital, Tegal Regency. The research employed an analytical observation with a cross-sectional design conducted from April to June 2021. The research method included the Widal test and filling out questionnaires.  Data were analyzed using univariate and chi-square tests. The results of this study revealed 14 positive patients with typhoid fever, with a Widal titer of 1/160 (40%) and a Widal titer of 1/320 in 21 people (60%). There was no significant relationship between the habit of handwashing and the incidence of typhoid fever (p = 0,076). Similarly, no significant relationship was found between the habit of eating outside the home and the incidence of typhoid fever (p = 0,144). However, a significant relationship was observed between environmental conditions around the house and the incidence of typhoid fever (p = 0,009). It is recommended that individuals improve personal hygiene and the environment around their homes to reduce Salmonella typhi infection.  Keywords: Salmonella typhi, typhoid fever, widal test